PENGUATAN DEMOKRASI PENDIDIKAN MELALUI PEMBELAJARAN KOLABORATIF DI SMA - Agus Tinus; Darus Salam; Dedy Suryadi (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
emocratic education has become a crucial demand in 21st-century learning, emphasizing active participation, equality, and students’ freedom of expression; however, classroom practices are still predominantly teacher-centered, limiting student engagement in the learning process. This study aims to analyze the strengthening of educational democracy through the implementation of collaborative learning practices at SMAN 2 Sampit, focusing on enhancing student participation, critical thinking skills, and the internalization of democratic values. This research employed a qualitative approach with a case study design, involving two teachers and thirty eleventh-grade students as research subjects. Data were collected through observation, in-depth interviews, and documentation over a two-month period. The data analysis followed systematic stages, including data reduction, data display, and conclusion drawing. The findings reveal that collaborative learning significantly increases students’ active participation in discussions, encourages confidence in expressing opinions, and fosters critical thinking through group interaction. Furthermore, this approach contributes to the internalization of democratic values such as tolerance, cooperation, and responsibility among students. In conclusion, collaborative learning is proven to be an effective pedagogical strategy in strengthening educational democracy in secondary school contexts. ABSTRAK Pendidikan demokratis menjadi salah satu tuntutan penting dalam pembelajaran abad ke-21 yang menekankan partisipasi aktif, kesetaraan, dan kebebasan berpendapat peserta didik, namun praktik pembelajaran di sekolah masih cenderung berpusat pada guru sehingga membatasi keterlibatan siswa. Penelitian ini bertujuan untuk menganalisis penguatan demokrasi pendidikan melalui praktik pembelajaran kolaboratif di SMAN 2 Sampit. Fokus penelitian ini adalah bagaimana implementasi pembelajaran kolaboratif dapat meningkatkan partisipasi, kemampuan berpikir kritis, serta nilai-nilai demokrasi siswa. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan 2 guru dan 30 siswa kelas XI, dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi selama dua bulan. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pembelajaran kolaboratif mampu meningkatkan partisipasi aktif siswa dalam diskusi, mendorong keberanian dalam menyampaikan pendapat, serta mengembangkan kemampuan berpikir kritis melalui interaksi kelompok. Selain itu, pembelajaran ini juga berkontribusi dalam menginternalisasi nilai-nilai demokrasi seperti toleransi, kerja sama, dan tanggung jawab. Dengan demikian, pembelajaran kolaboratif terbukti menjadi strategi yang efektif dalam memperkuat demokrasi pendidikan di lingkungan sekolah menengah.